The Antecedents and Challenges of Innovation in Sustainable Development Projects: Systematic Review - Hassan, Afaf (Environmental Management and Sustainable Development, 2021)
This study demonstrates the antecedents and challenges of innovation in sustainable development (SD) projects. In particular, a systematic literature review is conducted to highlight the challenges of innovation, that can suppress the efficient attainment of innovation benefits, in SD projects. The findings indicate that the positive benefits of innovation, in SD projects, are applying new strategies, developing new management practices, increasing interests and commitments of project team members, obtaining a better quality, attaining competitive advantages, introducing active influencers, establishing more engagement and collaborative work among team members, and satisfying project stakeholders. On the other side, innovation challenges that could act as barriers to achieve these benefits, in SD projects, are innovation resistance, stakeholders’ requirements, pressure from clients to meet the SD project goals, diverse project environment, dynamic and unstable markets, project structure and characteristics, compliance with the common goals between innovation and sustainable development projects, and less management support and commitment for innovation. In brief, if project team members could overcome these challenges, innovation could be adopted and implemented effectively in sustainable development projects.